Investigation of microhardness properties of the multi-walled carbon nanotube additive MgB2 structure by using the vickers method - Kaya, Naki; Cavdar, Sukru; Ozturk, Ozgur; Ada, Hakan; Koralay, Haluk (Elsevier BV, 2021)
Abstract In this study, the effect of multi-walled carbon nanotube doping to MgB2 compound on microhardness properties of MgB2 was investigated by using solid-state reaction method. The amount of multi-walled carbon nanotubes was chosen as 0, 1, 2, 3 and 4% by weight of total MgB2. All samples were obtained by sintered at 650 °C temperatures. The microhardness properties of the samples obtained were examined using the Vickers method. At the same time, the samples obtained were analyzed according to Meyer’s Law, proportional sample resistance (PSR) model, Hays-Kendall (HK) approach and elastic/plastic deformation (EPD) model. Samples were found to exhibit indentation size effect (ISE) behavior. It was understood that the multi-walled carbon nanotubes doped to the samples made MgB2 softer by reducing the intergranular bonding of the MgB2 structure. In addition, it was found that the force applied to the samples caused both plastic and elastic deformation on the samples.
Keywords: Superconductivity; Multi-Walled Carbon Nanotube; MgB2; Vickers Microhardness